Planet Omar : Accidental trouble magnet - Mian, Zanib; Mafaridik, Nasaya (Great Britain : Hodder, 2019)
"Imaginative Omar goes through the ups and downs of starting a new school and making new friends with the help of his wonderful (and silly) Muslim family"--Provided by publisher.
"First published in Great Britain by Hodder and Stoughton, 2019"--T.p. verso.
"First released under the title The Muslims"--Author profile.
Booklist starred
Publishers Weekly
Booklist starred, November 2019
Publishers Weekly, November 2019
Keywords: Families -- England -- Juvenile fiction; Friendship -- Juvenile fiction; Muslims -- Juvenile fiction; Schools -- Juvenile fiction; Family life -- England -- Fiction; Friendship -- Fiction; Humorous stories; Muslims -- Fiction; Schools -- Fiction; Family life -- England -- Fiction; Friendship -- Fiction; Muslims -- Fiction; School stories; England -- Juvenile fiction; England -- Fiction; England -- Fiction; Humorous fiction